Pembuatan Permen Jelly Berbahan Dasar Labu Kuning - mila yulia herosian; muhammad agung anggoro (Universitas Pahlawan Tuanku Tambusai, 2022)
Community service is carried out in Sekip Village, Lubuk Pakam District, Deli Serdang Regency with the goals and targets to be achieved, namely housewives can utilize local food ingredients, namely pumpkin (Cucurbita Moschata) to be processed into products that have added value, so that later it can become an economic resource, and can improve the economy. The service is carried out for 1 day in two stages. The first stage is to provide counseling about the value and benefits of pumpkin for health, and the use of pumpkin to be the basic ingredient for making jelly. The second stage is to provide jelly making training. The benefits that can be taken from this activity are increasing public awareness and ability to use pumpkin as an ingredient for making jelly and being able to foster entrepreneurial motivation, especially for the people of Sekip Village.